PLUME-DERIVED RARE GASES IN 380 MA CARBONATITES FROM THE KOLA REGION (RUSSIA) AND THE ARGON ISOTOPIC COMPOSITION IN THE DEEP MANTLE - Marty B.; Tolstikhin I.; Zimmermann J.L.; Kamensky I.L.; Nivin V.; Balaganskaya E. (My University, 1998)
In an effort to document the source of the parental melts to carbonatites, we have measured rare gases in 380 Ma carbonatites and associated mineral assemblages from the Kola Peninsula, eastern part of the Baltic shield in Russia. These series were emplaced during widespread Devonian magmatism when several large ultrabasic–alkaline–carbonatite massifs were formed. 4He/3He ratios vary from 1×106 to 1×107 in the bulk He extracted by melting of samples from three localities, including the large Kovdor massif. A comparison of measured abundances of 3He and 4He with those expected from in-situ production revealed a large (up to 105 times) excess of 3He, implying a significant contribution from a mantle-derived 3He-bearing fluid. Crushing of these samples allowed extraction of fluids with 4He/3He ratios down to 38,000, lower than those of mid-ocean ridge basalts and in the range of 4He/3He observed in 3He-rich ocean island basalts (OIBs) related to mantle plumes. 20Ne/22Ne up to 12.1±0.2 are higher than the atmospheric value of 9.80, implying the occurrence of primordial (solar-type) neon in the carbonatite source. 20Ne/22Ne and 21Ne/22Ne ratios display a good correlation, with the regression line close to (slightly to the right of) the Loihi Seamount correlation. Extrapolation of the regression to solar 20Ne/22Ne of 13.8 gives a 21Ne/22Ne of 0.045 for the plume end-member, well below the mid-ocean ridge basalt (MORB) source (upper mantle) end-member of 0.07. The measured 40Ar/36Ar ratios up to 2790 correlate very well with the Ne isotopic ratios, and the best estimate of the 40Ar/36Ar ratio of the plume source is within 5000±1000. Although the 3He/22Ne ratio in the plume source appears to be comparable to the solar value within a factor of 2, the 22Ne/36Ar ratio, computed from Ne–Ar isotope correlation, is two orders of magnitude lower than the solar value. Such difference is unlikely to be due to magmatic fractionation since the observed 4He/40Ar* ratios are close to values expected for radiogenic production and accumulation in the mantle source. It may rather represent a characteristic of the plume source. The isotope composition of light noble gases in samples from ultrabasic–alkaline rocks of the Kola Peninsula, and associated carbonatites, indicate a contribution of material with lower time-integrated (U + Th)/(3He, 22Ne) and (40K/36Ar) ratios than those in the asthenospheric upper mantle, the subcontinental lithosphere, and the continental crust. The location of such material is likely to be below the convective mantle supplying MORB magmas, and reflects the contribution of a plume source material to Kola carbonatitic magmatism. These data support models which advocate a structure of the Earth heterogeneous in its refractory/volatile content.
Keywords: Devonian; Paleozoic::Devonian; Палеозой::Девонская